Exhaled Breath Condensate: A Promising Source for Biomarkers of Lung Disease - Yan Liang; Samantha M. Yeligar; Lou Ann S. Brown (The Scientific World Journal)
Exhaled breath condensate (EBC) has been increasingly studied as a noninvasive research method for sampling the alveolar and airway space and is recognized as a promising source of biomarkers of lung diseases. Substances measured in EBC include oxidative stress and inflammatory mediators, such as arachidonic acid derivatives, reactive oxygen/nitrogen species, reduced and oxidized glutathione, and inflammatory cytokines. Although EBC has great potential as a source of biomarkers in many lung diseases, the low concentrations of compounds within the EBC present challenges in sample collection and analysis. Although EBC is viewed as a noninvasive method for sampling airway lining fluid (ALF), validation is necessary to confirm that EBC truly represents the ALF. Likewise, a dilution factor for the EBC is needed in order to compare across subjects and determine changes in the ALF. The aims of this paper are to address the characteristics of EBC; strategies to standardize EBC sample collection and review available analytical techniques for EBC analysis.